Characterization and modeling of silicon devices for RF applications - Teo, Tee Hui (2010)
The objective ofthis research is to carry out a thorough study of the characterization and modeling of silicon devices for RFIC applications. This work will be beneficial to both Integrated Circuit (IC) design and device development. The present study investigates both passive and active devices in two widely used silicon technologies, namely CMOS and Silicon (Si)/SiGe HBT. For these devices, new direct extraction techniques are discussed, and physically meaningful and unique parameters are obtained. Due to the lack of comprehensive analysis and experimental data in the literature for differential symmetrical spiral inductors, one main focus ofthis work is the design and characterization of a full set of such inductors. In addition, the conventional equivalent circuit for asymmetrical on-chip spiral inductor is extracted using a new direct extraction technique. This technique is verified to be effective for a library of spiral inductors with a wide range of device geometries. Moreover, the direct extraction technique is also extended to more advanced equivalent circuits for onchip spiral inductors.